2022
DOI: 10.22159/ajpcr.2022.v15i7.44718
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Refractive Errors Among Secondary School Children in an Urban Setup: A Prospective and Observational Study

Abstract: Objective: The aim of the study was to determine the prevalence of refractive errors and their types by their age, sex, and class among the students of secondary school in an urban area of state of Punjab, North India. Methods: A cross-sectional study was done on a total of 1545 school children, aged between 10 and 16 years studying in 6th–10th class. Sample size included 822 males and 723 females. Snellen’s distant test types and self-illuminated streak retinoscope were used for this study. Results: Cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Bhutia et al investigated 15,954 children aged 14-17 years and found REs in 1,069 (6.7%) subjects; myopia was most commonly observed RE in 335 (31.1%) children, followed by astigmatism in 317 (29.4%) participants and hypermetropia in 29 (2.6%) subjects in East Sikkim of Northeast India[24].In our study, out of 224 male participants, 77 (34.4%) have REs, and out of 196 female study subjects, 70 (35.7%) have REs. Singh et al also found REs in 287 (34.91%) males out of 822 observed and in 257 (35.55%) females out of 723 examined[25]. This study is important because it throws light on the prevalence of REs among children between seven and 15 years of age.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Bhutia et al investigated 15,954 children aged 14-17 years and found REs in 1,069 (6.7%) subjects; myopia was most commonly observed RE in 335 (31.1%) children, followed by astigmatism in 317 (29.4%) participants and hypermetropia in 29 (2.6%) subjects in East Sikkim of Northeast India[24].In our study, out of 224 male participants, 77 (34.4%) have REs, and out of 196 female study subjects, 70 (35.7%) have REs. Singh et al also found REs in 287 (34.91%) males out of 822 observed and in 257 (35.55%) females out of 723 examined[25]. This study is important because it throws light on the prevalence of REs among children between seven and 15 years of age.…”
mentioning
confidence: 52%
“…In our study, out of 224 male participants, 77 (34.4%) have REs, and out of 196 female study subjects, 70 (35.7%) have REs. Singh et al also found REs in 287 (34.91%) males out of 822 observed and in 257 (35.55%) females out of 723 examined [ 25 ]. This study is important because it throws light on the prevalence of REs among children between seven and 15 years of age.…”
Section: Discussionmentioning
confidence: 99%